Pengaruh Green Accounting, Kinerja Lingkungan, Struktur Modal dan Ukuran Perusahaan Terhadap Kinerja Keuangan (Studi Pada Perusahaan Subsektor Batu Bara, Gas & Minyak Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Monica Delima; Irda Rosita; Endrawati (Balance : Jurnal Akuntansi dan Bisnis, 2025)
The purpose of this study is to determine the influence of green accounting, environmental performance, capital structure, and firm size on financial performance. The data analysis method used in this study is a quantitative method and uses panel data regression analysis techniques. The population in this study is subsector coal, gas, and oil listed on the Indonesia Stock Exchange in 2020-2023. All data was then taken based on the purposive sampling method so that a sample of 17 companies per year was obtained. The results show that green accounting, environmental performance, and firm size has no effect on financial performance, capital structure has an effect on financial performance. This research is hoped to benefit companies by improving the quality of financial report and to provide knowledge or information to regulators in making decisions. Apart from that, researchers can contribute to the development of science related to accounting.